Tomato SlERF.A1, SlERF.B4, SlERF.C3 and SlERF.A3, Members of B3 Group of ERF Family, Are Required for Resistance to Botrytis cinerea - Ouyang, Zhigang; Liu, Shixia; Huang, Lihong; Hong, Yongbo; Li, Xiaohui; Huang, Lei; Zhang, Yafen; Zhang, Huijuan; Li, Dayong; Song, Fengming (Frontiers in Plant Science, 2016)
The Ethylene-Responsive Factors (ERFs) comprise a large family of transcriptional factors that play critical roles in plant immunity. Gray mold disease caused by Botrytis cinerea, a typical necrotrophic fungal pathogen, is the serious disease that threatens tomato production worldwide. However, littler is known about the molecular mechanism regulating the immunity to B. cinerea in tomato. In the present study, virus-induced gene silencing (VIGS)-based functional analyses of 18 members of B3 group (also called Group IX) in tomato ERF family were performed to identify putative ERFs that are involved in disease resistance against Botrytis cinerea. VIGS-based silencing of either SlERF.B1 or SlERF.C2 had lethal effect while silencing of SlERF.A3 (Pit4) significantly suppressed vegetative growth of tomato plants. Importantly, silencing of SlERF.A1, SlERF.A3, SlERF.B4 or SlERF.C3 resulted in increased susceptibility to B. cinerea, attenuated the B. cinerea-induced expression of jasmonic acid/ethylene-mediated signaling responsive defense genes and promoted the B. cinerea-induced H2O2 accumulation. However, silencing of SlERF.A3 also decreased the resistance against Pseudomonas syringae pv. tomato (Pst) DC3000 but silencing of SlERF.A1, SlERF.B4 or SlERF.C3 did not affect the resistance to this bacterial pathogen. Expression of SlERF.A1, SlERF.A3, SlERF.B4 or SlERF.C3 was induced by B. cinerea and by defense signaling hormones such as salicylic acid, methyl jasmonate and 1-aminocyclopropane-1-carboxylic acid (an ethylene precursor). SlERF.A1, SlERF.B4, SlERF.C3 and SlERF.A3 proteins were found to localize in nucleus of cells and possess transactivation activity in yeasts. These data suggest that SlERF.A1, SlERF.B4 and SlERF.C3, three previously uncharacterized ERFs in B3 group, and SlERF.A3, a previously identified ERF with function in immunity to Pst DC3000, play important roles in resistance against B. cinerea in tomato.